KEDUDUKAN HUKUM INFORMED CONSENT DALAM PEMENUHAN HAK PASIEN DI RUMAH SAKIT - Ardityo Purdianto Kristiawan (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2021)
Informed Consent is the approval of medical action given by the patient or his / her closest family after receiving a detailed explanation of the medical action to be performed on the patient. This is regulated in Law Number 29 Year 2004 Concerning Medical Practice, Paragraph 2, Article 45. Informed Consent is required for various medical actions, such as surgery (surgery), invasive procedures, and other high-risk measures. However, in its implementation there are still obstacles where there is a mismatch between the reality and the intended legality, both in terms of the completeness of the form, the quality of data filling, and the content of the information provided. This is caused by several causes, among others; There is a lack of understanding of medical personnel, medics, and patients about informedconsent, barriers to the medical language provided, in addition to constraints onunderstanding and patient education and the existence of patient disease status The legal position of patients and doctors is basically equal because they both have rights and obligations. For this reason, the legal position of patients in informed consent in terms of health laws and consumer protection laws is a position that must be protected as regulated therein. Each can exercise their rights and obligations freely without pressure from any party. In addition to improving the implementation of informed consent in health facilities, socialization is needed to medical staff and patients about its benefits. In addition, it is important to reconstruct the laws and regulations so that it can be guaranteed that the patient's rights are fulfilled for medical treatment and that there is legal protection for them.